2019
DOI: 10.1186/s12944-019-1139-8
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral systems for statin delivery: a review

Abstract: The oral route of drug administration is the most common and convenient route for dosing statin drugs, and, in fact, most medications, because of ease of drug delivery, patient compliance, and cost-effectiveness. However, the oral administration of statin drugs has disadvantages such as hepatic first-pass metabolism and degradation within the gastrointestinal tract that limit their overall bioavailability. This review introduces several diverse non-oral delivery methods for the administration of statins. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…To date, the only Food and Drug Administration (FDA)approved route of administration for statins is oral (Korani et al, 2019). Generally, statins are rapidly absorbed following administration, reaching peak plasma concentration within 4 h in immediate-release formulations (Wiggins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the only Food and Drug Administration (FDA)approved route of administration for statins is oral (Korani et al, 2019). Generally, statins are rapidly absorbed following administration, reaching peak plasma concentration within 4 h in immediate-release formulations (Wiggins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This result may be explained by the fact that a portion of the SV was metabolized into SVA in the liver by plasma lipase, leading to an increase in the amount of SVA reaching systemic circulation. Recently, several strategies have been developed to increase the concentration of SV and SVA in plasma by altering the release rate of SV and using parenteral systems such as sustained‐release tablet, enteric‐coated tablets, buccal patches and transdermal niosomal gelation (Bal et al, 2012; Korani et al, 2019; Vyas et al, 2010; Yoshinari et al, 2007). These methods have increased the relative oral bioavailability of SV to a certain extent (2–5 times).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, if inpatients are treated with statins, treatment might be withdrawn if they are transferred to ICUs, although intravenously administered statins are licensed if not widely available. 7 Whenever statins are withdrawn, their beneficial effects on the host response can be rapidly lost. 8 For example, cardiovascular investigators who studied patients hospitalized with acute myocardial infarction 15–20 years ago found that those who had been treated with statins as outpatients and whose statins were continued after hospital admission had lower mortality rates than those who had never received statins.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of statin treatment based only on outpatient information does not take into account the effects of statin withdrawal after hospital admission. Moreover, if inpatients are treated with statins, treatment might be withdrawn if they are transferred to ICUs, although intravenously administered statins are licensed if not widely available 7 . Whenever statins are withdrawn, their beneficial effects on the host response can be rapidly lost 8 .…”
Section: Discussionmentioning
confidence: 99%